Fiber sizing agent composition, fiber bundle, fiber product, and composite material

JP7651614B2Active Publication Date: 2025-03-26SANYO CHEM IND LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023093814
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-08-02
Filing Date
2023-06-07
Publication Date
2025-03-26
Estimated Expiration
2039-07-30

AI Technical Summary

Benefits of technology

【0007】 本発明の繊維用集束剤組成物は繊維とマトリックス樹脂との接着性を向上させることができ、かつ、本発明の繊維用集束剤組成物(C)を用いることにより、高い集束性を保持しながら、毛羽立ちの少ない繊維束及び繊維製品を得られるという効果を奏する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651614000001
    Figure 0007651614000001
  • Figure 0007651614000002
    Figure 0007651614000002
  • Figure 0007651614000003
    Figure 0007651614000003
Patent Text Reader

Abstract

To provide a sizing agent composition for fibers, capable of providing high adhesion between fibers and a matrix resin, and also capable of forming fiber bundles with reduced fluffing while retaining high sizing properties.SOLUTION: The present invention provides: a sizing agent composition for fibers (C) comprising an epoxy resin (A) having an aromatic ring and not having a (meth)acryloyl group and a (meth)acrylate (B); a fiber bundle comprising at least one fiber selected from the group consisting of carbon fibers, glass fibers, aramid fibers, ceramic fibers, metal fibers, mineral fibers, and slag fibers, the fibers being treated with the sizing agent composition for fibers (C); a fiber bundle comprising the at least one fiber, an epoxy resin (A) having an aromatic ring and not having a (meth)acryloyl group and / or a reaction product of the epoxy resin (A) having an aromatic ring and not having a (meth)acryloyl group, and a (meth)acrylate (B) and / or a reaction product of the (meth)acrylate (B); and a fiber product comprising the fiber bundle.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fiber sizing agent composition, a fiber bundle, a fiber product, and a composite material. [Background technology]

[0002] Composite materials containing various matrix resins and various fibers are widely used in fields such as sports equipment, leisure goods, and aircraft. The fibers used in these composite materials include glass fibers, carbon fibers, ceramic fibers, metal fibers, mineral fibers, rock fibers, slag fibers, etc. These fibers are usually provided with a sizing agent to prevent fluffing and thread breakage during the processing step to produce the composite materials. However, when a conventional sizing agent is used for fibers, if the matrix resin is a thermosetting resin or a thermoplastic resin, such as a vinyl ester resin or an unsaturated polyester resin, the adhesion between the fibers and the matrix resin becomes insufficient, resulting in a problem of insufficient physical properties of the obtained composite material. To solve this problem, it is known to use a fiber sizing agent in which an epoxy resin is dispersed in an aqueous medium by a urethane resin having an alkoxypolyoxyethylene structure and an epoxy group (e.g., Patent Document 1), and to use polyethyleneimine as a sizing agent (e.g., Patent Document 2).

[0003] In order to improve the physical properties of composite materials, it is important that the adhesion between the fibers and the matrix resin is high in order to effectively utilize the characteristics of the fibers, and that the fiber bundle has good bundling ability and little fuzzing in terms of the handleability of the fiber bundle. Therefore, there is a demand for a sizing agent that can improve the adhesion between the fibers and the matrix resin, improve the handleability of the fibers, and form a fiber bundle with little fuzzing. The sizing agents proposed in Patent Documents 1 and 2 have problems in that they are unable to sufficiently improve the adhesion between the fibers and the matrix resin, are unable to sufficiently improve the bundling ability, and are unable to sufficiently suppress the fuzzing of the fiber bundles. In addition, when a composite material is produced using the sizing agents proposed in Patent Documents 1 and 2, if the matrix resin is a highly viscous thermoplastic resin, the impregnation ability of the matrix resin cannot be sufficiently improved, causing uneven impregnation and voids, resulting in a problem that the strength of the obtained composite material is insufficient. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-249562 A [Patent Document 2] Japanese Patent Application Publication No. 03-065311 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a fiber sizing agent composition which has high adhesion between the fibers and a matrix resin, and which is capable of producing a fiber bundle with little fuzz while maintaining high sizing ability. [Means for solving the problem]

[0006] As a result of investigations aimed at achieving the above object, the present inventors arrived at the present invention. That is, the present invention relates to a fiber sizing agent composition (C) containing an epoxy resin (A) having an aromatic ring but not having a (meth)acryloyl group and a (meth)acrylate (B); a fiber bundle obtained by treating at least one type of fiber selected from the group consisting of carbon fibers, glass fibers, aramid fibers, ceramic fibers, metal fibers, mineral fibers, and slug fibers with the fiber sizing agent composition (C); a fiber bundle comprising at least one type of fiber selected from the group consisting of carbon fibers, glass fibers, aramid fibers, ceramic fibers, metal fibers, mineral fibers, and slug fibers, a reaction product of an epoxy resin (A) having an aromatic ring but not having a (meth)acryloyl group and / or an epoxy resin (A) having an aromatic ring but not having a (meth)acryloyl group, and a (meth)acrylate (B) and / or a reaction product of the (meth)acrylate (B); a fiber product comprising this fiber bundle; and a composite material comprising this fiber bundle and / or this fiber product and a matrix resin. Effect of the Invention

[0007] The fiber sizing composition of the present invention can improve the adhesion between the fibers and the matrix resin, and by using the fiber sizing composition (C) of the present invention, it is possible to obtain fiber bundles and fiber products with little fuzz while maintaining high sizing ability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The fiber sizing agent composition (C) of the present invention contains an epoxy resin (A) having an aromatic ring and no (meth)acryloyl group, and a (meth)acrylate (B). In this specification, "(meth)acrylate" means acrylate and / or methacrylate, and "(meth)acryloyl" means acryloyl and / or methacryloyl.

[0009] The epoxy resin (A) having an aromatic ring and no (meth)acryloyl group which constitutes the fiber sizing agent composition (C) of the present invention is not particularly limited in its chemical structure as long as it is an epoxy resin having an aromatic ring and an epoxy group in the molecule and no (meth)acryloyl group.

[0010] Examples of the epoxy resin (A) having an aromatic ring and not having a (meth)acryloyl group that constitutes the fiber sizing agent composition (C) of the present invention include diepoxides (A1) having an aromatic ring and novolac-type epoxy resins (A2).

[0011] Examples of the diepoxide (A1) having an aromatic ring include a diglycidyl ether (A11) having an aromatic ring, a diglycidyl ester (A12) having an aromatic ring, and a diglycidyl amine (A13) having an aromatic ring.

[0012] Examples of the diglycidyl ether (A11) having an aromatic ring include diglycidyl ethers of dihydric phenols and diglycidyl ethers of dihydric alcohols having an aromatic ring. Examples of diglycidyl ethers of dihydric phenols include condensates (including polycondensates) of dihydric phenols having 6 to 30 carbon atoms with epichlorohydrin, both ends of which are glycidyl ethers. Examples of dihydric phenols include bisphenols (such as bisphenol F, bisphenol A, bisphenol B, bisphenol AD, bisphenol S, and halogenated bisphenol A), catechin, resorcinol, hydroquinone, 1,5-dihydroxynaphthalene, dihydroxybiphenyl, octachloro-4,4'-dihydroxybiphenyl, tetramethylbiphenyl, and 9,9'-bis(4-hydroxyphenyl)fluorene. Examples of diglycidyl ethers of dihydric alcohols having an aromatic ring include arylaliphatic diols having 8 to 30 carbon atoms, alkylene oxide (hereinafter, "alkylene oxide" may be abbreviated as "AO") adducts of arylaliphatic diols, and condensates (including polycondensates) of AO adducts of dihydric phenols with epichlorohydrin, both of which have glycidyl ethers at their terminals. Examples of the aromatic aliphatic diol having 8 to 30 carbon atoms include 1,4-bis(2-hydroxyethyl)benzene, di[9-(3-hydroxypropyl)-9-fluorenyl]methane, and diphenylpropanediol. Examples of the AO adduct of an aromatic aliphatic diol include an AO (1 to 20 mol) adduct of 1,4-bis(2-hydroxyethyl)benzene, an AO (1 to 20 mol) adduct of di[9-(3-hydroxypropyl)-9-fluorenyl]methane, and an AO (1 to 20 mol) adduct of diphenylpropanediol. Examples of AO adducts of dihydric phenols include AO adducts of bisphenols (such as bisphenol F, bisphenol A, bisphenol B, bisphenol AD, bisphenol S, and halogenated bisphenol A), catechin, resorcinol, hydroquinone, 1,5-dihydroxynaphthalene, dihydroxybiphenyl, octachloro-4,4'-dihydroxybiphenyl, tetramethylbiphenyl, and 9,9'-bis(4-hydroxyphenyl)fluorene. Among these, an AO (1 to 20 mol) adduct of bisphenol A is preferred. Examples of AO include ethylene oxide (hereinafter, "ethylene oxide" may be abbreviated as "EO"), 1,2-propylene oxide (hereinafter, "1,2-propylene oxide" may be abbreviated as "PO"), 1,2-butylene oxide (hereinafter, "1,2-butylene oxide" may be abbreviated as "1,2-BO"), and 1,4-butylene oxide (hereinafter, "1,4-butylene oxide" may be abbreviated as "1,4-BO").

[0013] The molar ratio of the dihydric phenol unit and / or dihydric alcohol unit {H removed from the hydroxyl group (-OH) of the dihydric phenol and dihydric alcohol} constituting the diglycidyl ether (A11) having an aromatic ring to the epichlorohydrin unit {total of the glycidyl ether group and the group (-CH(OH)CH2-) obtained by ring-opening polymerization of epichlorohydrin} {(dihydric phenol unit and / or dihydric alcohol unit):(epichlorohydrin unit)} is expressed as n:n+1. n is preferably 1 to 10, more preferably 1 to 8, and particularly preferably 1 to 5. The diglycidyl ether (A11) may be a mixture of n=1 to 10 (e.g., a mixture having different degrees of polycondensation).

[0014] Examples of the diglycidyl ester (A12) having an aromatic ring include diglycidyl esters of aromatic dicarboxylic acids and diglycidyl esters of araliphatic dicarboxylic acids. Examples of diglycidyl esters of aromatic dicarboxylic acids include condensates (including polycondensates) of aromatic dicarboxylic acids {terephthalic acid, isophthalic acid, phthalic acid, alkylisophthalic acids (for example, 4-methylisophthalic acid, etc.), naphthalenedicarboxylic acids (naphthalenedicarboxylic acids having two carboxyl groups on different rings, such as 1,5-naphthalenedicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 1,7-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, and 2,6-naphthalenedicarboxylic acid; naphthalenedicarboxylic acids having two carboxyl groups on the same ring, such as 1,2-naphthalenedicarboxylic acid and 1,4-naphthalenedicarboxylic acid), etc.} with epichlorohydrin, which have two glycidyl groups. Examples of diglycidyl esters of araliphatic dicarboxylic acids include condensates (including polycondensates) of araliphatic dicarboxylic acids (such as 1,4-phenylenediacetic acid) with epichlorohydrin, which have two glycidyl groups. The molar ratio of the aromatic dicarboxylic acid unit and / or aromatic aliphatic dicarboxylic acid unit {H removed from the carboxyl group (-COOH) of the dicarboxylic acid} constituting the diglycidyl ester (A12) having an aromatic ring to the epichlorohydrin unit {total of the glycidyl ether group and the group (-CH(OH)CH2-) formed by ring-opening polymerization of epichlorohydrin} {(aromatic dicarboxylic acid unit and / or aliphatic dicarboxylic acid unit):(epichlorohydrin unit)} is expressed as n:n+1. n is preferably 1 to 10, more preferably 1 to 8, and particularly preferably 1 to 5. The diglycidyl ester (A12) may be a mixture of n=1 to 10.

[0015] Examples of the diglycidylamine (A13) having an aromatic ring include N-glycidyl compounds (N,N-diglycidylaniline, N,N-diglycidyltoluidine, etc.) obtained by reacting an aromatic amine having 6 to 20 carbon atoms and 2 to 4 active hydrogen atoms (aniline, toluidine, etc.) and an aromatic aliphatic amine having 7 to 20 carbon atoms and 2 to 4 active hydrogen atoms (1,3- or 1,4-xylylenediamine, etc.) with epichlorohydrin. The molar ratio of the aromatic amine unit and / or aromatic aliphatic amine unit {a compound obtained by removing two H from the amino group (-NH2) possessed by the aromatic amine and aromatic aliphatic amine} to the epichlorohydrin unit (total of the glycidyl ether unit and the epichlorohydrin ring-opening polymerization unit) constituting the diglycidylamine (A13) {(aromatic amine unit):(epichlorohydrin unit)} is expressed as n:n+1. n is preferably 1 to 10, more preferably 1 to 8, and particularly preferably 1 to 5. The diglycidylamine (A13) may be a mixture of n=1 to 10.

[0016] As these diepoxides (A1), from the viewpoint of improving the strength of molded articles of the composite material, diglycidyl ethers (A11) are preferred, more preferably diglycidyl ethers of dihydric phenols, particularly preferably diglycidyl ethers of bisphenols, and most preferably diglycidyl ethers of bisphenol A (bisphenol A-type epoxy resins).

[0017] Examples of the novolac type epoxy resin (A2) include orthocresol novolac type epoxy resin, phenol novolac type epoxy resin, and halogenated phenol novolac type epoxy resin.

[0018] The novolac type epoxy resin (A2) can be obtained, for example, by reacting a novolac type epoxy resin such as an orthocresol novolac resin, a phenol novolac resin, or a halogenated phenol novolac resin with epichlorohydrin in the presence of an alkali, and is also available as a commercial product. Examples of commercially available orthocresol novolac type epoxy resins include Sumiepoxy ESCN-195X and ESCN-220 manufactured by Sumitomo Chemical Co., Ltd., Araldite ECN1273, ECN-1280, and ECN-1299 manufactured by Nippon Ciba-Geigy Ltd., and EOCN-101, EOCN-102, and EOCN-103 manufactured by Nippon Kayaku Co., Ltd. Examples of phenol novolac type epoxy resins include Epicoat 152 and Epicoat 154 manufactured by Yuka Shell Epoxy Co., Ltd., and YDPN-601 and YDPN-602 manufactured by Tohto Kasei Co., Ltd. Examples of halogenated phenol novolac type epoxy resins include BREN, which is a brominated phenol novolac type epoxy resin manufactured by Nippon Kayaku Co., Ltd.

[0019] When a composite material is produced using the fiber sizing composition (C) of the present invention and the matrix resin is a thermosetting resin, the epoxy equivalent (g / eq) of the epoxy resin (A) having an aromatic ring and no (meth)acryloyl group constituting the fiber sizing composition (C) of the present invention is preferably 100 to 1000, more preferably 100 to 800, from the viewpoint of improving the adhesion between the fiber and the matrix resin. Here, the epoxy equivalent is a value measured in accordance with JIS K 7236.

[0020] When a composite material is produced using the fiber sizing agent composition (C) of the present invention and the matrix resin is a thermoplastic resin, the epoxy equivalent (g / eq) of the epoxy resin (A) having an aromatic ring and no (meth)acryloyl group that constitutes the fiber sizing agent composition (C) of the present invention is preferably 500 to 2,000, more preferably 700 to 1,500, from the viewpoints of improving the adhesion between the fiber and the matrix resin and preventing the generation of voids.

[0021] The (meth)acrylate (B) constituting the fiber sizing agent composition (C) of the present invention is not particularly limited in its chemical structure as long as it is a (meth)acrylate, and may include a (meth)acrylate (B1) having no oxyalkylene group in the molecule and a (meth)acrylate (B2) having an oxyalkylene group in the molecule. In addition, the (meth)acrylate (B) preferably does not have a glycidyl ether group in the molecule.

[0022] From the viewpoint of improving the adhesion between the fiber and the matrix resin, the (meth)acrylate (B1) having no oxyalkylene group in the molecule preferably has two or more (meth)acryloyl groups, and includes bifunctional (meth)acrylates (B11), trifunctional (meth)acrylates (B12) and tetrafunctional or higher (meth)acrylates (B13).

[0023] The difunctional (meth)acrylate (B11) may, for example, be a difunctional non-aromatic (meth)acrylate or a difunctional aromatic (meth)acrylate.

[0024] Examples of difunctional non-aromatic (meth)acrylates include diesters of polyhydric alcohols having 2 to 20 carbon atoms and more than 2 valences (preferably 2 to 8 valences) and (meth)acrylic acid. Such compounds include 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, and 2,4-dimethyl-1,5-pentanediol di(meth)acrylate.

[0025] Examples of the difunctional aromatic (meth)acrylate include a diester of a diglycidyl ether of a dihydric phenol and (meth)acrylic acid. Examples of such compounds include di(meth)acrylates of diglycidyl ethers of bisphenols (such as bisphenol F, bisphenol A, bisphenol B, bisphenol AD, bisphenol S, and halogenated bisphenol A), di(meth)acrylates of diglycidyl ethers of catechin, di(meth)acrylates of diglycidyl ethers of resorcinol, di(meth)acrylates of diglycidyl ethers of hydroquinone, di(meth)acrylates of diglycidyl ethers of 1,5-dihydroxynaphthalene, di(meth)acrylates of diglycidyl ethers of dihydroxybiphenyl, di(meth)acrylates of diglycidyl ethers of octachloro-4,4'-dihydroxybiphenyl, di(meth)acrylates of diglycidyl ethers of tetramethylbiphenyl, and di(meth)acrylates of diglycidyl ethers of 9,9'-bis(4-hydroxyphenyl)fluorene.

[0026] The trifunctional (meth)acrylate (B12) may, for example, be a trifunctional non-aromatic (meth)acrylate or a trifunctional aromatic (meth)acrylate.

[0027] Examples of trifunctional non-aromatic (meth)acrylates include triesters of tri- or higher hydric (preferably tri- to octahydric) polyhydric alcohols having 2 to 20 carbon atoms and (meth)acrylic acid. Examples of such compounds include trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, and sorbitol tri(meth)acrylate.

[0028] An example of the trifunctional aromatic (meth)acrylate is a triester product of a trifunctional aromatic epoxy resin and (meth)acrylic acid. Examples of such compounds include tri(meth)acrylate of N,N,O-triglycidyl-p-aminophenol, tri(meth)acrylate of N,N,O-triglycidyl-m-aminophenol, tri(meth)acrylate of N,N,O-triglycidyl-4-amino-m-cresol, tri(meth)acrylate of N,N,O-triglycidyl-5-amino-o-cresol, and tri(meth)acrylate of 1,1,1-tris(4-hydroxyphenyl)ethane triglycidyl ether.

[0029] Examples of the tetrafunctional or higher (meth)acrylate (B13) include tetrafunctional or higher non-aromatic (meth)acrylates and tetrafunctional or higher aromatic (meth)acrylates.

[0030] Examples of tetrafunctional or higher non-aromatic (meth)acrylates include tetraesters, pentaesters, and hexaesters of tetravalent or higher (preferably tetravalent to octavalent) polyhydric alcohols having 2 to 20 carbon atoms and (meth)acrylic acid. Examples of such compounds include pentaerythritol tetra(meth)acrylate, sorbitol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol propionate tetra(meth)acrylate, sorbitol penta(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, sorbitol hexa(meth)acrylate, and caprolactone-modified dipentaerythritol hexa(meth)acrylate.

[0031] Examples of the tetrafunctional or higher aromatic (meth)acrylate include tetraesters of tetrafunctional or higher aromatic epoxy resins and (meth)acrylic acid. Examples of such compounds include tetra(meth)acrylate of N,N,N',N'-tetraglycidylaminodiphenylmethane, tetra(meth)acrylate of N,N,N',N'-tetraglycidyl1,4-bis[2-(4-aminophenyl)-2-propyl]benzene, tetra(meth)acrylate of 1,1,2,2-tetrakis[4-(glycidyloxy)phenyl]ethane, polyesters of phenol novolac epoxy resins, which are multifunctional epoxy resins, and (meth)acrylic acid, and polyesters of cresol novolac epoxy resins and (meth)acrylic acid.

[0032] The (meth)acrylate (B2) having an oxyalkylene group in the molecule preferably has two or more (meth)acryloyl groups from the viewpoint of improving the adhesion between the fiber and the matrix resin, and includes difunctional (meth)acrylates (B21), trifunctional (meth)acrylates (B22), tetrafunctional to hexafunctional (meth)acrylates (B23) and heptafunctional to decafunctional (meth)acrylates (B24).

[0033] Examples of the bifunctional (meth)acrylate (B21) include a diester of an AO adduct of a dihydric or higher polyhydric alcohol (preferably di- to octahydric) and (meth)acrylic acid, a diester of an AO adduct of a dihydric alcohol or a dihydric phenol and (meth)acrylic acid, and an epoxy acrylate which is a reaction product of a diglycidyl ether of an AO adduct of a dihydric alcohol or a dihydric phenol and acrylic acid.

[0034] Examples of diesters of AO adducts of dihydric or higher polyhydric alcohols (preferably dihydric to octahydric) and (meth)acrylic acid include di(meth)acrylates of AO adducts of ethylene glycol, di(meth)acrylates of AO adducts of 1,2- or 1,3-propanediol, di(meth)acrylates of AO adducts of trimethylolpropane, and di(meth)acrylates of AO adducts of glycerin. An example of a diesterification product of an AO adduct of a dihydric alcohol or a dihydric phenol and (meth)acrylic acid is a di(meth)acrylate of an AO adduct of bisphenol A. Commercially available epoxy acrylates, which are reaction products of diglycidyl ethers of AO adducts of dihydric alcohols or dihydric phenols with acrylic acid, include Epoxy Ester 40EM, Epoxy Ester 70PA, Epoxy Ester 200PA, Epoxy Ester 3002M, and Epoxy Ester 3002A (all manufactured by Kyoeisha Chemical Co., Ltd.).

[0035] In the above compound, it is not necessary that all of the hydroxyl groups of the polyhydric alcohol are reacted with (meth)acrylic acid and / or AO, and some hydroxyl groups may remain unreacted. AO includes those having 2 to 4 carbon atoms, and specific examples thereof include EO, PO, 1,2-BO, and 1,4-BO. The number of moles of AO added is preferably 2 to 100, and more preferably 3 to 50, from the viewpoint of improving the bundling property and the adhesion between the fiber and the matrix resin.

[0036] Examples of the trifunctional (meth)acrylate (B22) include triesters of AO adducts of trihydric or higher (preferably trihydric to octahydric) polyhydric alcohols and (meth)acrylic acid, etc. Examples of such compounds include tri(meth)acrylates of EO adducts of trimethylolpropane, etc. AO includes those having 2 to 4 carbon atoms, and specific examples thereof include EO, PO, 1,2-BO, and 1,4-BO. The number of moles of AO added is preferably 2 to 100, and more preferably 3 to 50, from the viewpoint of improving the bundling property and the adhesion between the fiber and the matrix resin.

[0037] Examples of the tetra- to hexafunctional (meth)acrylates (B23) include tetraesters, pentaesters and hexaesters of AO adducts of tetrahydric or higher (preferably tetrahydric to octahydric) polyhydric alcohols and (meth)acrylic acid. Examples of such compounds include tetra(meth)acrylate of an EO adduct of dipentaerythritol, penta(meth)acrylate of an EO adduct of dipentaerythritol, and penta(meth)acrylate of a PO adduct of dipentaerythritol. AO includes those having 2 to 4 carbon atoms, and specific examples thereof include EO, PO, 1,2-BO, and 1,4-BO. The number of moles of AO added is preferably 2 to 100, and more preferably 3 to 50, from the viewpoint of improving the bundling property and the adhesion between the fiber and the matrix resin.

[0038] Examples of the hepta-to-decafunctional (meth)acrylate compounds (B24) include hydroxyl group-containing compounds among the monofunctional (meth)acrylates (B21) to trifunctional (meth)acrylates (B23) and compounds obtained by a urethane reaction between a hydroxyl group-containing monofunctional (meth)acrylate (e.g., hydroxyethyl (meth)acrylate, etc.) as needed and an isocyanate compound having two or more isocyanate groups. Examples of such compounds include a compound obtained by reacting penta(meth)acrylate, an AO adduct of dipentaerythritol, with hexamethylene diisocyanate.

[0039] In the present invention, the number of (meth)acryloyl groups in one molecule of the (meth)acrylate (B) is preferably 2 or more, more preferably 2 to 4, and particularly preferably 2, from the viewpoint of improving the adhesion between the fiber and the matrix resin.

[0040] In the present invention, when the matrix resin of the composite material is a thermosetting resin, the (meth)acrylic equivalent (g / eq) of the (meth)acrylate (B) is, from the viewpoint of improving the adhesion between the fiber and the matrix resin, preferably 150 to 10000, more preferably 200 to 8000. Here, the (meth)acrylic equivalent means a value obtained by dividing the molecular weight of the (meth)acrylate (B) by the number of (meth)acryloyl groups in one molecule.

[0041] In the present invention, when the matrix resin of the composite material is a thermoplastic resin, the (meth)acrylic equivalent (g / eq) of the (meth)acrylate (B) is preferably 150 to 1,000, more preferably 200 to 800, from the viewpoints of improving the adhesion between the fiber and the matrix resin and preventing the generation of voids.

[0042] In the present invention, the (meth)acrylate (B) preferably has a hydroxyl group from the viewpoint of improving the bundling ability and the adhesion between the fiber and the matrix resin. The number of hydroxyl groups that the (meth)acrylate (B) has is preferably 2 or more, more preferably 2 to 10, and particularly preferably 2 to 5, from the viewpoint of improving the bundling ability and the adhesion between the fiber and the matrix resin.

[0043] In the present invention, from the viewpoint of improving the bundling ability and the adhesion between the fibers and the matrix resin, the hydroxyl value (mgKOH / g) of the (meth)acrylate (B) is preferably from 0 to 500, more preferably from 0 to 100. Here, the hydroxyl value means the mass (mg) of potassium hydroxide equivalent to the hydroxyl groups in 1 g of a sample measured according to JIS K 0070-1992.

[0044] When a composite material is produced using the fiber sizing agent composition (C) of the present invention and the matrix resin of the composite material is a thermosetting resin, from the viewpoints of improving the adhesion between the fiber and the matrix resin and reducing fuzzing, the (meth)acrylate (B) is preferably a (meth)acrylate (B2) having an oxyalkylene group, more preferably an acrylate having an oxyalkylene group, and particularly preferably a bifunctional acrylate having an oxyalkylene group. When a composite material is produced using the fiber sizing agent composition (C) of the present invention and the matrix resin of the composite material is a thermoplastic resin, from the viewpoints of improving the adhesion between the fiber and the matrix resin and preventing the occurrence of voids, the (meth)acrylate (B) is preferably a (meth)acrylate (B1) having no oxyalkylene group, more preferably an aromatic (meth)acrylate having no oxyalkylene group, and particularly preferably an aromatic acrylate having no oxyalkylene group.

[0045] The weight ratio (A) / (B) of the epoxy resin (A) having an aromatic ring and no (meth)acryloyl group and the (meth)acrylate (B) constituting the fiber sizing agent composition (C) of the present invention is preferably 10 / 90 to 90 / 10, more preferably 20 / 80 to 80 / 20, from the viewpoint of improving the sizing ability and the adhesion between the fiber and the matrix resin. When the ratio is 10 / 90 or more and 90 / 10 or less, the adhesion with the matrix resin is improved.

[0046] Furthermore, the fiber sizing agent composition (C) of the present invention preferably contains a polyester resin (D) having a bisphenol skeleton and a polyoxyethylene chain. In the present invention, the polyoxyethylene chain means a compound in which two or more oxyethylene groups are bonded in succession. The polyester resin (D) is not particularly limited in terms of its chemical structure as long as it has a bisphenol skeleton and a polyoxyethylene chain. From the viewpoints of sizing ability and reducing fuzzing, however, it is preferably a polyester resin composed of a dicarboxylic acid or its anhydride (d1) and a diol (d2), and more preferably a polyester resin containing, as constituent monomers, a dicarboxylic acid or its anhydride (d1) and a diol (d22) having a bisphenol skeleton and a polyoxyethylene chain. The polyester resin (D) may be used alone or in combination of two or more kinds.

[0047] Examples of the dicarboxylic acid or anhydride thereof (d1) constituting the polyester resin (D) include aliphatic dicarboxylic acids (d11), aromatic dicarboxylic acids (d12) and acid anhydrides thereof.

[0048] Examples of the aliphatic dicarboxylic acid (d11) include linear saturated aliphatic dicarboxylic acids (d111), linear unsaturated aliphatic dicarboxylic acids (d112), alicyclic dicarboxylic acids (d113), and dimer acids (a14).

[0049] Examples of the chain saturated aliphatic dicarboxylic acid (d111) include linear or branched chain saturated aliphatic dicarboxylic acids having 2 to 22 carbon atoms (oxalic acid, malonic acid, succinic acid, glutaric acid, methylsuccinic acid, ethylsuccinic acid, dimethylmalonic acid, α-methylglutaric acid, β-methylglutaric acid, 2,4-diethylglutaric acid, isopropylmalonic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decanedicarboxylic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, tridecanedicarboxylic acid, tetradecanedicarboxylic acid, hexadecanedicarboxylic acid, octadecanedicarboxylic acid, icosanedicarboxylic acid, decylsuccinic acid, dodecylsuccinic acid, and octadecylsuccinic acid, etc.).

[0050] Examples of the chain unsaturated aliphatic dicarboxylic acid (d112) include linear or branched chain unsaturated aliphatic dicarboxylic acids having 4 to 22 carbon atoms (maleic acid, fumaric acid, citraconic acid, mesaconic acid, dodecenylsuccinic acid, pentadecenylsuccinic acid, octadecenylsuccinic acid, etc.).

[0051] Examples of the alicyclic dicarboxylic acid (d113) include alicyclic dicarboxylic acids having 7 to 14 carbon atoms (1,3- or 1,2-cyclopentanedicarboxylic acid, 1,2-, 1,3-, or 1,4-cyclohexanedicarboxylic acid, 1,2-, 1,3-, or 1,4-cyclohexanediacetic acid, and dicyclohexyl-4,4'-dicarboxylic acid).

[0052] The dimer acid (d114) may be a dimer of a chain unsaturated aliphatic carboxylic acid having 8 to 24 carbon atoms (such as oleic acid, linoleic acid, and linolenic acid).

[0053] Examples of the aromatic dicarboxylic acid (d12) include aromatic dicarboxylic acids having 8 to 14 carbon atoms (terephthalic acid, isophthalic acid, phthalic acid, phenylmalonic acid, phenylsuccinic acid, β-phenylglutaric acid, α-phenyladipic acid, β-phenyladipic acid, biphenyl-2,2'- or 4,4'-dicarboxylic acid, naphthalenedicarboxylic acid, sodium 5-sulfoisophthalate, and potassium 5-sulfoisophthalate).

[0054] Examples of the anhydrides of dicarboxylic acids include anhydrides of the above aliphatic dicarboxylic acids (d11) or aromatic dicarboxylic acids (d12), such as succinic anhydride, maleic anhydride, and phthalic anhydride.

[0055] The dicarboxylic acids and anhydrides thereof (d1) may be used alone or in combination of two or more kinds. Among these, from the viewpoint of focusing ability, preferred are linear saturated aliphatic dicarboxylic acids (d111), linear unsaturated aliphatic dicarboxylic acids (d112) and aromatic dicarboxylic acids (d12), more preferred are oxalic acid, malonic acid, succinic acid, adipic acid, sebacic acid, maleic acid, fumaric acid, terephthalic acid, isophthalic acid and phthalic acid, and particularly preferred are adipic acid, maleic acid, fumaric acid, terephthalic acid and isophthalic acid.

[0056] As the diol (d2) constituting the polyester resin (D), a diol (d22) having a bisphenol skeleton and a polyoxyethylene chain is preferred from the viewpoints of sizing ability and reducing fluffing.

[0057] In the diol (d22) having a bisphenol skeleton and a polyoxyethylene chain, examples of the bisphenol compound constituting the bisphenol skeleton include bisphenol A, bisphenol F, and bisphenol S. In the diol (d22) having a bisphenol skeleton and a polyoxyethylene chain, the number of repeating units of the oxyethylene group constituting the polyoxyethylene chain is preferably 5 to 100, and more preferably 5 to 80, from the viewpoint of reducing fluffing. The diol (d22) having a bisphenol skeleton and a polyoxyethylene chain may have, in addition to the polyoxyethylene chain, an oxyalkylene group having a carbon number of 2 to 4. Examples of the oxyalkylene group include an oxyethylene group, an oxypropylene group, and an oxybutylene group. Specific examples of the diol (d22) having a bisphenol skeleton and a polyoxyethylene chain include adducts of the above bisphenol compounds with AO having 2 to 4 carbon atoms.

[0058] The diol (d2) may be used alone or in combination of two or more kinds. Among the diols (d2), from the viewpoint of focusing ability, AO adducts of bisphenol A, AO adducts of bisphenol F and AO adducts of bisphenol S are preferred, and AO adducts of bisphenol A and AO adducts of bisphenol F are more preferred.

[0059] The viscosity of the polyester resin (D) at 100° C. is preferably from 0.5 to 50 Pa·s, more preferably from 1 to 30 Pa·s, and particularly preferably from 3 to 20 Pa·s. If the viscosity is in the range of 0.5 to 50 Pa·s, better sizing properties and emulsion stability can be obtained. The viscosity of the polyester resin (D) at 100°C is measured using a Brookfield viscometer (BL type) in accordance with JIS K7117-1:1999 (corresponding to ISO2555:1990).

[0060] The polyester resin (D) preferably has a number average molecular weight (hereinafter abbreviated as Mn) of 1,000 to 50,000. When Mn is 1,000 or more, sufficient sizing ability is exhibited, and when Mn is 50,000 or less, affinity for water is high and emulsion stability is excellent. Incidentally, Mn is measured by GPC. Mn is more preferably from 1,500 to 30,000, and particularly preferably from 2,000 to 20,000. If it is within this range, the sizing ability and affinity for water will be more excellent.

[0061] The GPC conditions used for measuring the Mn of the polyester resin (D) are, for example, as follows. Model: Alliance (Liquid chromatograph manufactured by Japan Waters Co., Ltd.) Column: Guardcolumn Super HL +TSK gel Super H4000 +TSK gel Super H3000 +TSK gel Super H2000 (All manufactured by Tosoh Corporation) Column temperature: 40℃ Detector: RI (Refractive Index) Eluent: Tetrahydrofuran Eluent flow rate: 0.6ml / min Sample concentration: 0.25% by weight Injection volume: 10μl Standard material: Polystyrene (manufactured by Tosoh Corporation; TSK STANDARD POLYSTYRENE)

[0062] The polyester resin (D) can be produced, for example, by charging a dicarboxylic acid or its anhydride (d1) and a diol (d2) in a predetermined molar ratio, and distilling off water under stirring at a reaction temperature of 100 to 250°C and a pressure of -0.1 to 1.2 MPa. The molar ratio of the dicarboxylic acid or its anhydride (d1) to the diol (d2) [dicarboxylic acid or its anhydride (d1) / diol (d2)] is preferably 0.7 to 1.5, more preferably 0.8 to 1.25, from the viewpoint of improving sizing ability while keeping Mn within the above range.

[0063] When producing the polyester resin (D), it is preferable to add a catalyst in an amount of 0.05 to 0.5% by weight based on the weight of the polyester. Examples of the catalyst include paratoluenesulfonic acid, dibutyltin oxide, tetraisopropoxy titanate, and potassium oxalate titanate, and from the viewpoints of reactivity and environmental impact, tetraisopropoxy titanate and potassium oxalate titanate are preferred, and potassium oxalate titanate is more preferred.

[0064] The fiber sizing agent composition (C) of the present invention may contain a surfactant (E) and other additives in addition to the epoxy resin (A), (meth)acrylate (B), and polyester resin (D).

[0065] The surfactant (E) may be added for the purpose of emulsifying the mixture of the epoxy resin (A) and the (meth)acrylate (B). Examples of the surfactant (E) include nonionic surfactants, anionic surfactants, cationic surfactants, amphoteric surfactants, etc. The surfactant (E) may be used alone or in combination of two or more kinds. Of the surfactants (E), from the viewpoint of ease of preparation of an aqueous emulsion, anionic surfactants, nonionic surfactants, and combinations of these are preferred. More preferred are alkylene oxide adducts of alkyl phenols (preferably alkyl groups having 9 to 15 carbon atoms), alkylene oxide adducts of aryl alkyl phenols (preferably alkyl groups having 2 to 10 carbon atoms, styrenated phenol, styrenated cumylphenol, styrenated cresol, etc.), Pluronic surfactants, sulfate salts of alkylene oxide adducts of alkyl phenols, sulfate salts of alkylene oxide adducts of aryl alkyl phenols, urethane joint compounds of the Pluronic surfactants, urethane joint compounds of alkylene oxide adducts of aryl alkyl phenols and polyethylene glycol, and mixtures thereof, and particularly preferred are alkylene oxide adducts of aryl alkyl phenols, sulfate salts of alkylene oxide adducts of aryl alkyl phenols, and mixtures thereof.

[0066] Other additives include lubricants, preservatives, and antioxidants. Examples of the smoothing agent include waxes (polyethylene, polypropylene, oxidized polyethylene, oxidized polypropylene, modified polyethylene, modified polypropylene, etc.), higher fatty acid (fatty acid having 6 to 30 carbon atoms) alkyl (alkyl having 1 to 24 carbon atoms) esters (methyl stearate, ethyl stearate, propyl stearate, butyl stearate, octyl stearate, stearyl stearate, etc.), higher fatty acids (fatty acid having 6 to 30 carbon atoms) (myristic acid, palmitic acid, stearic acid, etc.), natural fats and oils (coconut oil, beef tallow, olive oil, rapeseed oil, etc.), and liquid paraffin. Preservatives include benzoic acid, salicylic acid, sorbic acid, quaternary ammonium salts, and imidazole. Antioxidants include phenols (such as 2,6-di-t-butyl-p-cresol), thiodipropionates (such as dilauryl 3,3'-thiodipropionate), and phosphites (such as triphenyl phosphite).

[0067] The preferred contents of the epoxy resin (A), the (meth)acrylate (B), the polyester resin (D), the surfactant (E) and other additives in the fiber sizing agent composition (C) of the present invention are as follows. From the viewpoint of improving the adhesion between the fibers and the matrix resin, the weight proportion of the epoxy resin (A) is preferably 1 to 90% by weight, more preferably 5 to 80% by weight, and particularly preferably 10 to 75% by weight, based on the weight of the solid content contained in the fiber sizing agent composition (C). From the viewpoint of improving the adhesion between the fibers and the matrix resin, the weight proportion of the (meth)acrylate (B) is preferably 1 to 90% by weight, more preferably 5 to 80% by weight, and particularly preferably 10 to 75% by weight, based on the weight of the solid content contained in the fiber sizing agent composition (C). From the viewpoint of sizing ability, the weight proportion of the polyester resin (D) is preferably 5 to 90% by weight, more preferably 10 to 70% by weight, based on the weight of the solid content contained in the fiber sizing agent composition (C). From the viewpoint of emulsion stability, the weight proportion of the surfactant (E) is preferably 0.1 to 40% by weight, more preferably 0.5 to 35% by weight, and particularly preferably 1 to 30% by weight, based on the weight of the solid content contained in the fiber sizing agent composition (C). The weight proportions of the other additives, such as the smoothing agent, preservative and antioxidant, based on the weight of the solid content contained in the fiber sizing agent composition (C), from the viewpoints of fluidity and stability over time, are preferably 0.01 to 20% by weight, more preferably 0.05 to 15% by weight, and particularly preferably 0.1 to 10% by weight.

[0068] The fiber sizing agent composition (C) of the present invention preferably contains an aqueous medium so as to be in the form of an aqueous solution or an aqueous emulsion. When an aqueous medium is contained, it is easy to adjust the amount of solid matter contained in the fiber sizing agent composition (C) to adhere to the fibers to an appropriate amount, so that a fiber bundle having even greater strength as a molded body of the composite material can be obtained. As the aqueous medium, known aqueous media can be used, and specific examples thereof include water and hydrophilic organic solvents [monohydric alcohols having 1 to 4 carbon atoms (methanol, ethanol, isopropanol, etc.), ketones having 3 to 6 carbon atoms (acetone, ethyl methyl ketone, methyl isobutyl ketone, etc.), glycols having 2 to 6 carbon atoms (ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, etc.) and their monoalkyl (carbon number 1 to 2) ethers, dimethylformamide, and alkyl acetates having 3 to 5 carbon atoms (methyl acetate, ethyl acetate, etc.)]. These may be used in combination of two or more kinds. Among these, from the viewpoint of safety etc., water and a mixed solvent of a hydrophilic organic solvent and water are preferred, and water is more preferred.

[0069] From the viewpoint of cost, etc., it is preferable that the fiber sizing agent composition (C) of the present invention is distributed at a high concentration and is distributed at a low concentration when a fiber bundle is produced. That is, by distributing the composition at a high concentration, transportation costs and storage costs can be reduced, and by treating the fibers at a low concentration, a fiber bundle that can increase the strength of a molded body of a composite material can be produced. The concentration of the high-concentration aqueous solution or emulsion (weight ratio of solid content to fiber sizing agent composition (C)) is preferably 20 to 80% by weight, more preferably 30 to 70% by weight, from the viewpoint of storage stability and the like. On the other hand, the concentration of the low-concentration aqueous solution or emulsion (weight ratio of solid content to fiber sizing agent composition (C)) is preferably 0.5 to 15% by weight, more preferably 1 to 10% by weight, from the viewpoint of ensuring an appropriate amount of sizing agent adhered during the production of fiber bundles.

[0070] The fiber sizing composition (C) of the present invention can be produced by mixing the epoxy resin (A) having an aromatic ring and no (meth)acryloyl group, the (meth)acrylate (B), and, if necessary, the aqueous medium, the polyester resin (D), the surfactant (E) and other additives in any order. When the composition contains an aqueous solvent, it is preferable to mix the components other than the aqueous medium in advance, and then add the aqueous medium to the mixture obtained to dissolve or emulsify the mixture.

[0071] When components other than the aqueous medium are mixed in advance, the temperature is preferably 20 to 90° C., more preferably 40 to 90° C., from the viewpoint of ease of mixing, and the same is also true for the temperature of the subsequent dissolution or emulsification dispersion. The time for the dissolving or emulsifying / dispersing is preferably 1 to 20 hours, and more preferably 2 to 10 hours.

[0072] There are no limitations on the mixing equipment, dissolving equipment, and emulsifying / dispersing equipment, and examples that can be used include stirring blades (blade shape: paddle type and three-stage paddle, etc.), Nauta mixers, ribbon mixers, conical blenders, mortar mixers, universal mixers (Universal Mixing Agitator 5DM-L, manufactured by San-Ei Seisakusho Co., Ltd., etc.), and Henschel mixers.

[0073] Examples of fibers to which the fiber sizing agent composition (C) of the present invention can be applied include known fibers such as glass fibers, carbon fibers, aramid fibers, ceramic fibers, metal fibers, mineral fibers, rock fibers, and slug fibers (such as those described in International Publication No. 2003 / 47830), and from the viewpoint of improving the strength of a molded body of a composite material, it is preferably at least one fiber selected from the group consisting of carbon fibers, glass fibers, aramid fibers, ceramic fibers, metal fibers, mineral fibers, and slug fibers, and more preferably carbon fibers. Two or more of these fibers may be used in combination.

[0074] The fiber bundle of the present invention is a fiber bundle (a fiber bundle comprising approximately 3,000 to 50,000 fibers) obtained by treating at least one type of fiber selected from the group consisting of carbon fibers, glass fibers, aramid fibers, ceramic fibers, metal fibers, mineral fibers, and slug fibers with the fiber sizing agent composition (C) of the present invention. That is, the fiber bundle of the present invention contains at least one type of fiber selected from the group consisting of carbon fibers, glass fibers, aramid fibers, ceramic fibers, metal fibers, mineral fibers, and slug fibers, an epoxy resin (A) having an aromatic ring and no (meth)acryloyl group and / or a reaction product of the epoxy resin (A), and a (meth)acrylate (B) and / or a reaction product of the (meth)acrylate (B). Examples of the reaction product of the epoxy resin (A) include a reaction product between epoxy resins (A) and a reaction product between the epoxy resin (A) and carbon fibers (such as a carboxyl group or a hydroxyl group in the carbon fibers). Examples of the reaction product of the (meth)acrylate (B) include a reaction product between (meth)acrylates (B).

[0075] The fiber treatment method may be a spray method or a dipping method. The amount (wt%) of the solid content of the fiber sizing agent composition (C) adhered to the fiber is preferably 0.05 to 5 wt%, more preferably 0.2 to 2.5 wt%, based on the weight of the fiber. Within this range, the strength of the molded product of the composite material can be further improved. The weight ratio of the epoxy resin (A) having an aromatic ring but no (meth)acryloyl group and the reaction product of the epoxy resin (A) to the (meth)acrylate (B) and the reaction product of the (meth)acrylate (B) (reaction product of (A) and (A) / reaction product of (B) and (B)) contained in the fiber bundle is preferably 10 / 90 to 90 / 10, and more preferably 20 / 80 to 80 / 20, from the viewpoint of improving bundling ability and adhesion between the fibers and the matrix resin. The weight ratio of the epoxy resin (A) having an aromatic ring and no (meth)acryloyl group and the reaction product of the epoxy resin (A) contained in the fiber bundle is, from the viewpoint of improving the adhesion between the fibers and the matrix resin, preferably 0.0005 to 4.5% by weight, more preferably 0.002 to 4% by weight, next more preferably 0.0025 to 3.75% by weight, next more preferably 0.005 to 2.25% by weight, next more preferably 0.01 to 2% by weight, and particularly preferably 0.02 to 1.875% by weight, based on the weight of the fibers. The weight proportion of the (meth)acrylate (B) and the reactant of the (meth)acrylate (B) contained in the fiber bundle is, from the viewpoint of improving the adhesion between the fiber and the matrix resin, preferably 0.0005 to 4.5 wt %, more preferably 0.002 to 4 wt %, next more preferably 0.0025 to 3.75 wt %, next more preferably 0.005 to 2.25 wt %, next more preferably 0.01 to 2 wt %, and particularly preferably 0.02 to 1.875 wt %, based on the weight of the fiber. From the viewpoint of bundling ability, the weight proportion of the polyester resin (D) contained in the fiber bundle is preferably 0.0025 to 4.5% by weight, more preferably 0.005 to 3.5% by weight, next more preferably 0.01 to 2.25% by weight, and particularly preferably 0.02 to 1.75% by weight, based on the weight of the fiber. The weight proportion of the surfactant (E) contained in the fiber bundle is, from the viewpoint of improving the adhesion between the fibers and the matrix resin, preferably 0.00005 to 2 weight %, more preferably 0.0002 to 1.75 weight %, next more preferably 0.00025 to 1.5 weight %, next more preferably 0.0005 to 1 weight %, next more preferably 0.001 to 0.875 weight %, and particularly preferably 0.002 to 0.75 weight %, based on the weight of the fibers.

[0076] The textile product of the present invention is made of the fiber bundle, and includes textile products obtained by processing the fiber bundle, such as woven fabrics, knitted fabrics, nonwoven fabrics (felt, mats, papers, etc.), chopped fibers, and milled fibers.

[0077] The composite material of the present invention contains the fiber bundle and / or fiber product of the present invention and a matrix resin. The matrix resin includes thermoplastic resins and thermosetting resins. Examples of thermoplastic resins include polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyamide, polystyrene, polyethersulfone, acrylonitrile-styrene resin, acrylonitrile-butadiene-styrene resin, acrylic resin, polycarbonate, polyetherimide, polyetheretherketone, polyacetal, polyphenylene oxide, and polyphenylene sulfide. Examples of the thermosetting resin include epoxy resin, unsaturated polyester resin, and vinyl ester resin. In the case of a thermosetting resin, the composite material may contain a catalyst. As the catalyst, any known catalyst can be used without limitation, and examples of the catalyst include those described in JP-A-2005-213337 when the thermosetting resin is an epoxy resin.

[0078] From the viewpoint of the strength of the composite material to be molded, the weight ratio of the matrix resin to the fiber bundles and fiber products (matrix resin / fiber bundles and fiber products) is preferably 10 / 90 to 90 / 10, more preferably 20 / 80 to 70 / 30, and particularly preferably 30 / 70 to 60 / 40. When a catalyst is contained, the content of the catalyst is preferably 0.01 to 10% by weight, more preferably 0.1 to 5% by weight, and particularly preferably 1 to 3% by weight, based on the matrix resin.

[0079] When the matrix resin is a thermoplastic resin, the composite material of the present invention can be obtained by a method of impregnating a fiber product of the present invention (woven fabric, knitted fabric, nonwoven fabric, etc.) with a thermally melted matrix resin (melting temperature: 60 to 150°C) or a matrix resin diluted with a solvent (acetone, methyl ethyl ketone, methyl isobutyl ketone, toluene, xylene, ethyl acetate, etc.) and molding it, or by a method of putting the fiber bundle of the present invention or chopped fibers obtained by cutting the fiber bundle into a molten thermoplastic matrix resin, kneading, and injection molding it, or the like. In addition, when the matrix resin is a thermosetting resin, it can be molded by heating and molding, and then solidifying at room temperature. The composite material does not need to be completely cured, but it is preferable that the molded composite material is cured to an extent that it can maintain its shape. After molding, it may be further heated to completely cure. EXAMPLES

[0080] The present invention will be further described below with reference to examples and comparative examples, but the present invention is not limited thereto. In the following, % means % by weight, and parts means parts by weight, unless otherwise specified.

[0081] Production Example 1 <Production of polyether polyol (b7-1)> 100 parts of 1,2-propanediol and 3 parts of a 50% aqueous solution of potassium hydroxide (manufactured by Toagosei Co., Ltd.) were charged into an autoclave, and after nitrogen replacement, the mixture was vacuum dehydrated at 120°C for 60 minutes to reduce the moisture content to 0.1% or less. Next, 865 parts of PO and 865 parts of EO were simultaneously injected at 105 to 130°C for about 3 hours, and the reaction was continued at the same temperature until the volatile content was 0.1% or less, and the mixture was vacuum dehydrated at 120°C for 60 minutes to reduce the moisture content to 0.05% or less. Water and an alkali adsorbent (Kyoward 600, manufactured by Kyowa Chemical Industry Co., Ltd.) were added to the reaction product obtained, and the mixture was filtered and then dehydrated by heating to obtain polyether polyol (b7-1). The Mn of the obtained polyether polyol (b7-1) was 1,400.

[0082] Production Example 2 <Production of polyether polyol diglycidyl ether (b7-2)> In a reaction vessel equipped with a thermometer, a stirrer, and a nitrogen gas inlet tube, 1540 parts of the polyether polyol (b7-1) prepared in Production Example 1, 420 parts of epichlorohydrin, and 182 parts of sodium hydroxide were charged and reacted for 5 hours at 50° C. under a nitrogen atmosphere with vigorous stirring. After the reaction, 730 parts of water was added, stirred for 10 minutes, and washed with water. After standing, the upper layer was separated and filtered, and excess epichlorohydrin was removed from the filtrate under reduced pressure to obtain 1600 parts of polyether polyol diglycidyl ether (b7-2) as a residue. The epoxy equivalent of this glycidyl ether was 890 g / eq.

[0083] Production Example 3 <Production of epoxy diacrylate (B-7)> Into a glass reaction vessel equipped with a heating / cooling / stirring device, a reflux condenser, a dropping funnel, and a thermometer, 320 parts of the polyether polyol diglycidyl ether (b7-2) prepared in Production Example 2 and 99.7 parts of toluene were charged and heated to 110°C to dissolve uniformly. Then, 25.8 parts of acrylic acid, 0.3 parts of triphenylphosphine and 0.03 parts of p-methoxyphenol were charged and reacted at 110° C. for 10 hours. The end point of the esterification was determined by the acid value, and after it was confirmed that the acid value was 1.0 mgKOH / g or less, the solution was cooled to 60° C. Furthermore, a mixed gas of nitrogen and oxygen, in which the oxygen concentration was adjusted to 8% by volume, was blown into the solution in order to inhibit polymerization, and the temperature was raised to 80° C. The toluene was distilled off under reduced pressure to obtain an epoxy diacrylate (B-7) having a hydroxyl group in the molecule.

[0084] Production Example 4 <Production of polyether polyol diacrylate (B-12)> A glass reaction vessel equipped with a heating / cooling / stirring device, a reflux condenser, a dropping funnel, and a thermometer was charged with 350 parts of "Newpol PE-75", an EO adduct (number average molecular weight 3500) of polypropylene glycol (number average molecular weight 2000), and 400 parts of toluene, which were then heated to 110°C to dissolve uniformly. Then, 14.5 parts of acrylic acid, 0.3 parts of triphenylphosphine and 0.03 parts of p-methoxyphenol were charged and reacted at 110° C. for 10 hours. The end point of the esterification was determined by the acid value, and after it was confirmed that the acid value was 1.0 mgKOH / g or less, the mixture was cooled to 80° C. Furthermore, in order to inhibit polymerization, a mixed gas of nitrogen and oxygen, in which the oxygen concentration was adjusted to 8% by volume, was passed through the liquid, and the toluene was distilled off under reduced pressure to obtain epoxy diacrylate (B-12).

[0085] Production Example 5 <Production of polyether polyol diacrylate (B-13)> Epoxy diacrylate (B-13) was obtained in the same manner as in Production Example 4, except that 350 parts of "Newpol PE-75" was changed to 800 parts of "Newpol PE-68", an EO adduct (number average molecular weight 8000) of polypropylene glycol (number average molecular weight 1750).

[0086] Production Example 6 <Production of polyether polyol diacrylate (B-14)> Epoxy diacrylate (B-14) was obtained in the same manner as in Production Example 4, except that 350 parts of "Newpol PE-75" was changed to 1,600 parts of "Newpol PE-108", an EO adduct (number average molecular weight 16,000) of polypropylene glycol (number average molecular weight 3,250).

[0087] Production Example 7 <Production of polyether polyol diglycidyl ether (b15-1)> A polyether polyol diglycidyl ether (b15-1) was obtained in the same manner as in Production Example 2, except that 1540 parts of polyether polyol (b7-1) was replaced with 3500 parts of "Newpol PE-75", an EO adduct (number average molecular weight 3500) of polypropylene glycol (number average molecular weight 2000). The epoxy equivalent of this glycidyl ether was 1800 g / eq.

[0088] Production Example 8 <Production of epoxy diacrylate (B-15)> In Production Example 3, 320 parts of the polyether polyol diglycidyl ether (b7-2) was changed to 1,800 parts of the polyether polyol diglycidyl ether (b15-1), 99.7 parts of toluene was changed to 600 parts, and 25.8 parts of acrylic acid was changed to 72 parts, in the same manner as in Production Example 2, to obtain an epoxy diacrylate (B-15) having a hydroxyl group in the molecule.

[0089] Production Example 9 <Production of polyether polyol diglycidyl ether (b16-1)> Polyether polyol diglycidyl ether (b16-1) was obtained in the same manner as in Production Example 2, except that 1540 parts of polyether polyol (b7-1) was replaced with 4000 parts of EO adduct (number average molecular weight 8000) "Newpol PE-68" of polypropylene glycol (number average molecular weight 1750) and 182 parts of sodium hydroxide was replaced with 100 parts. The epoxy equivalent of this glycidyl ether was 4060 g / eq.

[0090] Production Example 10 <Production of epoxy diacrylate (B-16)> In Production Example 3, 320 parts of the polyether polyol diglycidyl ether (b7-2) was changed to 2,030 parts of polyether polyol diglycidyl ether (b16-1), 99.7 parts of toluene was changed to 600 parts, and 25.8 parts of acrylic acid was changed to 72 parts, in the same manner as in Production Example 2, to obtain an epoxy diacrylate (B-16) having a hydroxyl group in the molecule.

[0091] Production Example 11 <Production of polyether polyol diglycidyl ether (b17-1)> A polyether polyol diglycidyl ether (b17-1) was obtained in the same manner as in Production Example 2, except that 1540 parts of the polyether polyol (b7-1) was replaced with 4000 parts of the EO adduct (number average molecular weight 16000) "Newpol PE-108" of polypropylene glycol (number average molecular weight 3250) and 182 parts of sodium hydroxide was replaced with 50 parts. The epoxy equivalent of this glycidyl ether was 16000 g / eq.

[0092] Production Example 12 <Production of epoxy diacrylate (B-17)> An epoxy diacrylate (B-17) was obtained in the same manner as in Production Example 2, except that in Production Example 3, 320 parts of the polyether polyol diglycidyl ether (b7-2) was changed to 4,000 parts of the polyether polyol diglycidyl ether (b17-1), 99.7 parts of toluene was changed to 600 parts, and 25.8 parts of acrylic acid was changed to 18 parts.

[0093] Production Example 13 <Production of bisphenol A EO 40 mole adduct (d2-1)> In a pressure-resistant reaction vessel equipped with a stirrer, a heating / cooling device, and a dropping bomb, 404 parts (1 mol) of bisphenol A EO 4 mol adduct "Newpol BPE-40" [manufactured by Sanyo Chemical Industries, Ltd.] and 2 parts of potassium hydroxide were charged, and after nitrogen replacement, the pressure was set to -0.08 MPa. The temperature was raised to 130°C, and EO 1584 parts (36 mol) was dropped over 6 hours while adjusting the pressure to 0.5 MPaG or less, and then aged at 130°C for 3 hours. Next, after cooling to 100°C, 30 parts of adsorption treatment agent "Kyoward 600" [manufactured by Kyowa Chemical Industry Co., Ltd.] were charged, and the mixture was stirred and treated at 100°C for 1 hour, and the adsorption treatment agent was filtered to obtain bisphenol A EO 40 mol adduct (d2-1).

[0094] Production Example 14 <Production of Polyester Resin (D-1)> 1264 parts (4 mol parts) of bisphenol A EO 2 mol adduct "Newpol BPE-20" [manufactured by Sanyo Chemical Industries, Ltd.], 830 parts (5 mol parts) of terephthalic acid, and 2 parts of tetraisoprox titanate were reacted in a glass reaction vessel at 170°C for 15 hours while distilling off water under reduced pressure to 0.001 MPa. 1928 parts (0.97 mol parts) of bisphenol A EO 40 mol adduct (d2-1) prepared in Production Example 4 were further added thereto, and the mixture was reacted for 10 hours at 180°C under reduced pressure to -0.1 MPa while removing water, to obtain 3800 parts of polyester resin (D-1). The number average molecular weight of polyester resin (D-1) was measured by the above method and was 4100, and the viscosity at 100°C was 4.5 Pa·s.

[0095] Production Example 15 <Surfactant (E-2)> In a reaction vessel equipped with a stirrer and a temperature controller, 992 parts by weight of EO adduct (number average molecular weight 8000) of polypropylene glycol (number average molecular weight 1750) "Newpol PE-68" [manufactured by Sanyo Chemical Industries, Ltd.] was added and replaced with nitrogen. The temperature was raised to 80°C under a dry nitrogen atmosphere, and 8 parts by weight of toluene diisocyanate "Coronate T-80" [manufactured by Nippon Polyurethane Industry Co., Ltd.] (hereinafter abbreviated as TDI) was added, followed by aging at 80°C for 5 hours to obtain nonionic surfactant (E-2).

[0096] Production Example 16 <Acrylic Modified Epoxy Resin (A'-2)> Bisphenol F type epoxy resin "jER807" [manufactured by Mitsubishi Chemical Corporation] (330 parts (1 mol)), acrylic acid (72 parts (1 mol)), and triethanolamine (0.4 parts) were reacted in a glass reaction vessel at 110°C for 5 hours to obtain 412 parts of one-terminal acrylic-modified epoxy resin (A'-2).

[0097] Examples 1 to 29 and Comparative Examples 1 to 8 The raw materials other than water, in the amounts shown in Tables 1 to 3, were uniformly dissolved in a universal mixer [universal mixer, manufactured by San-Ei Manufacturing Co., Ltd.] for 30 minutes while controlling the temperature at 60°C. Water was then added dropwise thereto over 6 hours to obtain 250 parts each of fiber sizing agent compositions (C-1) to (C-29) according to the examples of the present invention and fiber sizing agent compositions (C'-1) to (C'-8) according to the comparative examples, each having an aqueous dispersion concentration of 40% by weight.

[0098] [Table 1]

[0099] [Table 2]

[0100] [Table 3]

[0101] The chemical compositions of the raw materials indicated by the symbols in Tables 1 to 3 are as follows: (A-1): Bisphenol A type epoxy resin [product name "JER1001", manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: 475 (g / eq)] (A-2): Bisphenol A type epoxy resin [product name "JER828", manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: 135 (g / eq)] (A-3): Phenol novolac type epoxy resin [product name "JER152", manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: 175 (g / eq)] (A-4): Bisphenol A type epoxy resin [product name "JER1002", manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: 650 (g / eq)] (A-5): Bisphenol A type epoxy resin [product name "JER1004", manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: 950 (g / eq)] (A'-1): Polyethylene glycol diglycidyl ether [product name "Epolite 400E", manufactured by Kyoeisha Chemical Co., Ltd., does not have an aromatic ring] (A'-2): One-terminal acrylic-modified epoxy resin (half ester) obtained by reacting the bisphenol F type epoxy resin obtained in Production Example 16 with acrylic acid. (B-1): Polyoxypropylene glycol diacrylate [product name "APG-400", manufactured by Shin-Nakamura Chemical Co., Ltd., (meth)acrylic equivalent: 268 g / eq] (B-2): Polyoxypropylene glycol (terminated epoxy acrylate) [product name "Epoxy Ester 200PA", manufactured by Kyoeisha Chemical Co., Ltd., diacrylate having two hydroxyl groups, (meth)acrylic equivalent: 224 g / eq, hydroxyl value: 250 mgKOH / g] (B-3): Polyoxyethylene glycol diacrylate [product name "Light Acrylate 9EG-A", manufactured by Kyoeisha Chemical Co., Ltd., (meth)acrylic equivalent: 254 g / eq] (B-4): Polyoxyethylene glycol diacrylate [product name "NK Ester A-1000", manufactured by Shin-Nakamura Chemical Co., Ltd., (meth)acrylic equivalent: 554 g / eq] (B-5): Ethylene oxide adduct diacrylate of bisphenol A [product name "Light Acrylate BP-4EAL", manufactured by Kyoeisha Chemical Co., Ltd., (meth)acrylic equivalent: 256 g / eq] (B-6): Propylene oxide adduct diacrylate of bisphenol A [product name "Light Acrylate BP-4PA", manufactured by Kyoeisha Chemical Co., Ltd., (meth)acrylic equivalent: 284 g / eq] (B-7): Epoxy diacrylate obtained in Production Example 3, (meth)acrylic equivalent: 944 g / eq, hydroxyl value: 59 mgKOH / g] (B-8): Polytetramethylene glycol diacrylate [product name "NK Ester A-PTMG-65", manufactured by Shin-Nakamura Chemical Co., Ltd., (meth)acrylic equivalent: 379 g / eq] (B-9): Ethylene oxide adduct diacrylate of bisphenol A [product name "NK Ester A-BPE-30", manufactured by Shin-Nakamura Chemical Co., Ltd., (meth)acrylic equivalent: 828 g / eq] (B-10): 2 mole acrylic acid adduct of bisphenol A diglycidyl ether [product name "Epoxy Ester 3000A", manufactured by Kyoeisha Chemical Co., Ltd., (meth)acrylic equivalent: 242 g / eq, hydroxyl value: 232 mgKOH / g] (B-11): 1,6-hexanediol diacrylate [product name "Light Acrylate 1.6HX-A", Kyoeisha Chemical Co., Ltd., (meth)acrylic equivalent: 113 g / eq] (B-12): Polyether polyol diacrylate obtained in Production Example 4, (meth)acrylic equivalent: 1804 g / eq, (B-13): Polyether polyol diacrylate obtained in Production Example 5, (meth)acrylic equivalent: 4054 g / eq, (B-14): Polyether polyol diacrylate obtained in Production Example 6, (meth)acrylic equivalent: 8054 g / eq, (B-15): Epoxy diacrylate obtained in Production Example 8, (meth)acrylic equivalent: 1880 g / eq, hydroxyl value: 30 mgKOH / g] (B-16): Epoxy diacrylate obtained in Production Example 10, (meth)acrylic equivalent: 4130 g / eq, hydroxyl value: 14 mgKOH / g] (B-17): Epoxy diacrylate obtained in Production Example 12, (meth)acrylic equivalent: 8130 g / eq, hydroxyl value: 7 mgKOH / g] (B-18): Ethylene oxide adduct of trimethylolpropane triacrylate [product name "Light Acrylate TMP-6EO-3A", manufactured by Kyoeisha Chemical Co., Ltd., (meth)acrylic equivalent: 169 g / eq] (B-19): Ethylene oxide adduct diacrylate of bisphenol A [product name "Light Acrylate BP-10EA", manufactured by Kyoeisha Chemical Co., Ltd., (meth)acrylic equivalent: 388 g / eq] (B-20): Polypropylene glycol diacrylate [product name "NK Ester APG-700", manufactured by Shin-Nakamura Chemical Co., Ltd., (meth)acrylic equivalent: 404 g / eq] (B-21): Diacrylate of propylene oxide / ethylene oxide adduct of bisphenol A [product name "NK Ester A-B1206PE", manufactured by Shin-Nakamura Chemical Co., Ltd., (meth)acrylic equivalent: 648 g / eq] (B-22): Bisphenol A diglycidyl ether methacrylate [product name "Epoxy Ester 3000A", Kyoeisha Chemical Co., Ltd., (meth)acrylic equivalent: 242 g / eq, hydroxyl value: 232 mgKOH / g] (D-1): Polyester resin obtained in Production Example 14 (E-1): An emulsifier containing a propylene oxide / ethylene oxide adduct of styrenated phenol, which is a nonionic surfactant, as a surfactant (E) [product name "Soprophor 796 / P", manufactured by Solvay Nicca Co., Ltd.] (E-2): Nonionic surfactant obtained in Production Example 15

[0102] The fiber sizing agent compositions of the Examples and Comparative Examples were used to evaluate the bundling ability of carbon fiber bundles, fluff, and adhesion to the matrix resin (vinyl ester resin or polyetherimide) by the following evaluation methods. In addition, for Examples 26 to 29 and Comparative Examples 6 to 8, the presence or absence of voids in the composite material molded bodies was also confirmed. The results are shown in Tables 1 to 3.

[0103] <Evaluation of convergence> (1) The fiber sizing agent composition was further diluted with water to a solid content of 1.5% by weight. Untreated carbon fibers (fineness 800 tex, filament count 12,000) were immersed in the aqueous solution to impregnate the sizing agent, and the fiber sizing agent was dried with hot air at 180°C for 3 minutes to produce a carbon fiber bundle. (2) The bundling property of the obtained carbon fiber bundle was evaluated in accordance with JIS L1096-1999 8.19.1 Method A (45° cantilever method). The larger the value (cm), the better the focusing ability. The bundle of carbon fibers obtained under these treatment conditions has a bundle focusing ability evaluated with a cantilever of generally 13 cm or more.

[0104] <Evaluation of fluff> (1) Carbon fiber bundles were prepared in the same manner as above. (2) Five chrome-plated stainless steel rods with a diameter of 2 mm were arranged in a zigzag pattern at 15 mm intervals so that the carbon fiber bundles passed over their surfaces at a contact angle of 120°. The carbon fiber bundle was placed between the stainless steel rods in a zigzag pattern and a tension of 1 kg was applied. Just before the take-up roll, the carbon fiber bundle was sandwiched between two 10 cm x 10 cm pieces of urethane foam with a load of 1 kg applied, and rubbed at a speed of 1 m / min for 5 minutes. (3) During this time, the weight of the fluff attached to the sponge was measured, and the weight of fluff per unit length of fiber (mg / m) was calculated. The smaller the weight of fluff per unit length, the less fluff is generated. The amount of fluff in the carbon fiber bundle obtained under these treatment conditions is generally preferably 0.05 mg / m or less.

[0105] <Evaluation of Adhesion (Vinyl Ester Resin)> The adhesion was evaluated by the microdroplet method. (1) Carbon fiber filaments were taken out from the carbon fiber bundle obtained by the above method and set in a sample holder. (2) Microdroplets of a matrix resin consisting of 100 parts by weight of vinyl ester resin "Lipoxy R-804" [manufactured by Showa Denko K.K.] and 25 parts by weight of hardener "Permec N" [manufactured by NOF Corporation] were formed on carbon fiber filaments, and the resin was hardened by heating at 25°C for 24 hours and 120°C for 5 hours to obtain a sample for measuring adhesion. (3) The measurement sample was set in a composite material interface property evaluation device HM410 [manufactured by Toei Sangyo Co., Ltd.], and the maximum pull-out load F when pulling out the microdroplets from the carbon fiber filament was measured. (4) The interfacial shear strength τ was calculated using the following formula. Interfacial shear strength τ (unit: MPa) = F / πdL [where F is the maximum pull-out load (N), d is the carbon fiber filament diameter (μm), and L is the particle diameter of the microdroplet in the pull-out direction (μm)] A larger interfacial shear strength τ means higher adhesiveness, and it is preferably 43 MPa or more, and more preferably 45 MPa or more.

[0106] <Adhesion evaluation (polyetherimide resin)> The adhesion was evaluated by the fragmentation method. (1) From the carbon fiber bundle obtained by the above method, carbon fiber filaments were taken out, sandwiched between laminated polyetherimide resin films "Superio (registered trademark)" E type [manufactured by Mitsubishi Plastics, Inc.] from above and below, and a molded plate with carbon fiber single yarns embedded therein was obtained using a heat press device. Dumbbell-shaped test pieces were punched out from this molded plate. (2) Both ends of the dumbbell-shaped sample were clamped, and a tensile force was applied in the fiber axis direction (longitudinal direction) to generate a strain of 12% at a speed of 2.0 mm / min. After that, the fragmented fiber length inside the sample, which had been made transparent by heating, was observed under a microscope. (3) Furthermore, the critical fiber length lc was calculated from the average broken fiber length la by the formula lc (μm) = (4 / 3) × la (μm). The strand tensile strength σ and the diameter d of the carbon fiber single yarn were measured, and the interfacial shear strength (IFSS), which is an index of the adhesive strength at the interface between the carbon fiber and the resin, was calculated by the following formula and listed in the table as the adhesion to the polyetherimide resin (MPa). In the examples, the test results were the average of the number of measurements n = 5. IFSS(MPa)=σ(MPa)×d(μm) / (2×lc)(μm) In the present invention, the IFSS is preferably in the range of 40 MPa or more, and more preferably 43 MPa or more.

[0107] <Checking for voids> A molded body of a composite material made of a thermoplastic resin was produced according to the following procedure, and the presence or absence of voids was confirmed. (1) The carbon fiber bundles obtained by the above method were arranged to prepare a carbon fiber sheet. (2) Next, four of the above carbon fiber sheets were placed between five sheets of "Superio (registered trademark)" E type resin film [manufactured by Mitsubishi Plastics, Inc.] so that the resin film and the carbon fiber sheet were laminated alternately, to prepare a laminate film. (3) The laminated film was placed in a hydraulic vacuum molding machine heated to 370°C and preheated under vacuum conditions for 4 minutes. After applying pressure at 10 MPa for 4 minutes, the film was cooled at 30°C for 2 minutes and demolded to obtain a molded body of the composite material made of the desired thermoplastic resin. (4) The obtained molded body of the composite material made of thermoplastic resin was cut with a cutter and visually inspected for the presence or absence of voids.

[0108] From the results in Tables 1 to 3, it can be seen that by using the fiber sizing agent compositions of Examples 1 to 29, it is possible to produce fiber bundles with little fuzz while maintaining high bundling ability, and the adhesion between the fibers and the matrix resin is improved. Furthermore, from the results of Examples 26 to 29, when a molded body of the composite material is produced, it is expected that the strength of the composite material will also be increased because no voids are generated. On the other hand, when the fiber sizing agent compositions of Comparative Examples 1-2 and 4-5, which do not contain an epoxy resin (A) having an aromatic ring, are used, it is found that the sizing ability of the fiber bundle is low. Among them, when the fiber sizing agent composition of Comparative Example 1, which uses only (meth)acrylate (B), is used, it is found that the amount of fluff on the fiber bundle is extremely large, and the adhesion between the fiber and the matrix resin in the composite material is also extremely low. In addition, when the fiber sizing agent composition of Comparative Example 2, which uses an epoxy resin (A'-1) without an aromatic ring and a (meth)acrylate (B), is used, it is found that the amount of fluff on the fiber bundle is small, but the adhesion between the fiber and the matrix resin in the composite material is low. In addition, when the fiber sizing agent compositions of Comparative Examples 4 and 5, which contain an epoxy resin (A'-2) having an aromatic ring and an acryloyl group, are used, it is found that the adhesion between the fiber and the matrix resin in the composite material is slightly high, but the amount of fluff on the fiber bundle is large. Furthermore, when the fiber sizing agent composition of Comparative Example 3, which uses only the epoxy resin (A) and does not contain the (meth)acrylate (B), is used, the sizing ability of the fiber bundle is somewhat high, but the adhesion between the fiber and the matrix resin in the composite material is also extremely low. Also, when the fiber sizing agent compositions of Comparative Examples 6 to 8 are used, the sizing ability of the fiber bundle is low, the amount of fluff is large, the adhesion between the fiber and the matrix resin in the composite material is extremely low, and voids are generated.

Claims

1. A fiber sizing agent composition (C) comprising an epoxy resin (A) having an aromatic ring and no (meth)acryloyl group, a (meth)acrylate (B), a surfactant (E) and water, The (meth)acrylate (B) is a (meth)acrylate (B1) having no oxyalkylene group in the molecule or a (meth)acrylate (B2) having an oxyalkylene group in the molecule, the (meth)acrylate (B1) is an ester of a dihydric to octahydric polyhydric alcohol and (meth)acrylic acid or a diester of a diglycidyl ether of bisphenol A and (meth)acrylic acid, When the (meth)acrylate (B1) is a diester of a diglycidyl ether of bisphenol A and (meth)acrylic acid, it does not include a half ester of a diglycidyl ether of bisphenol A and (meth)acrylic acid. When the (meth)acrylate (B2) is a bifunctional (meth)acrylate (B21) having an oxyalkylene group in the molecule, the (meth)acrylate (B21) is a diester of an alkylene oxide adduct of a di- to octahydric polyalcohol and (meth)acrylic acid, a diester of an alkylene oxide adduct of a dihydric phenol and acrylic acid, or a reaction product of a diglycidyl ether of an alkylene oxide adduct of a dihydric alcohol or a dihydric phenol and acrylic acid.

2. The fiber sizing agent composition (C) according to claim 1, wherein a weight ratio of the epoxy resin (A) having an aromatic ring and no (meth)acryloyl group to the (meth)acrylate (B) (epoxy resin (A) / (meth)acrylate (B)) is 10 / 90 to 90 / 10.

3. 3. The fiber sizing agent composition (C) according to claim 1 or 2, wherein the (meth)acrylate (B) is a (meth)acrylate having two or more (meth)acryloyl groups.

4. The fiber sizing composition (C) according to any one of claims 1 to 3, further comprising a polyester resin (D) having a bisphenol skeleton and a polyoxyethylene chain.

5. A fiber bundle obtained by treating at least one type of fiber selected from the group consisting of carbon fibers, glass fibers, aramid fibers, ceramic fibers, metal fibers, mineral fibers, and slug fibers with the fiber sizing agent composition (C) according to any one of claims 1 to 4.

6. At least one type of fiber selected from the group consisting of carbon fibers, glass fibers, aramid fibers, ceramic fibers, metal fibers, mineral fibers, and slug fibers; an epoxy resin (A) having an aromatic ring and no (meth)acryloyl group and / or a reaction product of an epoxy resin (A) having an aromatic ring and no (meth)acryloyl group; (Meth)acrylate (B) and / or a reaction product of (meth)acrylate (B), A fiber bundle comprising a surfactant (E), The (meth)acrylate (B) is a (meth)acrylate (B1) having no oxyalkylene group in the molecule or a (meth)acrylate (B2) having an oxyalkylene group in the molecule, the (meth)acrylate (B1) is an ester of a dihydric to octahydric polyhydric alcohol and (meth)acrylic acid or a diester of a diglycidyl ether of bisphenol A and (meth)acrylic acid, When the (meth)acrylate (B1) is a diester of a diglycidyl ether of bisphenol A and (meth)acrylic acid, it does not include a half ester of a diglycidyl ether of bisphenol A and (meth)acrylic acid. A fiber bundle, in which the (meth)acrylate (B2) is a bifunctional (meth)acrylate (B21) having an oxyalkylene group in the molecule, the (meth)acrylate (B21) is a diester of an alkylene oxide adduct of a di- to octahydric polyalcohol and (meth)acrylic acid, a diester of an alkylene oxide adduct of a dihydric phenol and acrylic acid, or a reaction product of a diglycidyl ether of an alkylene oxide adduct of a dihydric alcohol or a dihydric phenol and acrylic acid.

7. A fiber product comprising the fiber bundle according to claim 5 or 6.

8. A composite material comprising the fiber bundle according to claim 5 or 6 and / or the fiber product according to claim 7 and a matrix resin.

Citation Information

Patent Citations

  • Finishing agent for carbon fiber

    JP1977110997A

  • Sizing agent for carbon fiber

    JP1990307979A

  • Carbon fiber chop

    JP1991065311A

  • Carbon fiber bundle

    JP2001348783A

  • Fiber preform for molding, fiber-reinforced plastic and method for producing the same

    JP2002037904A